2012
DOI: 10.4003/006.030.0117
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Cryptic Diversity in the Indo-West Pacific Gastropod GenusLunella(Turbinidae) using Elliptic Fourier Analysis*

Abstract: Morphological variation in shell shape was quantitatively evaluated among newly identifi ed cryptic species in two species complexes (coronata and cinerea groups) belonging to the gastropod genus Lunella (Turbinidae) using elliptic Fourier descriptors (EFDs). Sympatric species of the coronata group show greater phenotypic diversity than the entirely allopatric cinerea group. We suggest that if morphological divergence is driven most strongly in sympatry, cryptic species are more likely to occur in taxa with al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
(63 reference statements)
1
8
0
Order By: Relevance
“…The moon turban snail ( Lunella granulata Gmelin, 1791), distributed primarily in the Indo-West Pacific area and ranging from Japan and Korea to China, preferentially inhabits rocky shores in the intertidal zone [3–5]. From an economic perspective, L. granulata is one of the most important species for the residents of the Penghu Archipelago and Taiwan due to its abundance and widespread distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The moon turban snail ( Lunella granulata Gmelin, 1791), distributed primarily in the Indo-West Pacific area and ranging from Japan and Korea to China, preferentially inhabits rocky shores in the intertidal zone [3–5]. From an economic perspective, L. granulata is one of the most important species for the residents of the Penghu Archipelago and Taiwan due to its abundance and widespread distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Combining these data with genetics, they unravel the origin and domestication history of ancient European cultivars of grapevine ( Vitis vinifera L.). Other authors have found the technique useful for uncovering cryptic diversity and for quantifying allometry (Langlade et al ., ; Feng et al ., ; Williams, Hall & Kuklinski, ).…”
Section: Introductionmentioning
confidence: 99%
“…Elliptic Fourier analysis was used to describe and quantify shell morphology (Williams et al 2012, Doyle et al 2018, Jackson & Claybourn 2018. Images of S. quadrata shells were acquired using a digital camera (K-S2, Ricoh, Japan), from which elliptic Fourier analysis was performed using SHAPE (Iwata & Ukai 2006).…”
Section: Quantification Of Shell Morphologymentioning
confidence: 99%